2017
DOI: 10.3390/nu9121351
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying and Gastrointestinal Transit Compared among Native and Hydrolyzed Whey and Casein Milk Proteins in an Aged Rat Model

Abstract: Little is known about how milk proteins affect gastrointestinal (GI) transit, particularly for the elderly, in whom digestion has been observed to be slowed. We tested the hypothesis that GI transit is faster for whey than for casein and that this effect is accentuated with hydrolysates, similar to soy. Adult male rats (18 months old) were fed native whey or casein, hydrolyzed whey (WPH) or casein (CPH), hydrolyzed blend (HB; 60% whey:40% casein), or hydrolyzed soy for 14 days then treated with loperamide, pru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
5
24
0
Order By: Relevance
“…Application of MPH to the colonic tissue increased motility by increasing the frequency of propagating synchronous contractions compared with the pretreatment control (Figure 2), and this effect persisted after washout. This finding was consistent with the enhanced fecal output associated with MPH compared with CPH in vivo (Dalziel et al, 2017b). However, MPH did not alter the frequency of nonsynchronous contractions in the proximal colon.…”
Section: Mph Increased the Frequency Of Propagating Synchronous Contrsupporting
confidence: 85%
See 2 more Smart Citations
“…Application of MPH to the colonic tissue increased motility by increasing the frequency of propagating synchronous contractions compared with the pretreatment control (Figure 2), and this effect persisted after washout. This finding was consistent with the enhanced fecal output associated with MPH compared with CPH in vivo (Dalziel et al, 2017b). However, MPH did not alter the frequency of nonsynchronous contractions in the proximal colon.…”
Section: Mph Increased the Frequency Of Propagating Synchronous Contrsupporting
confidence: 85%
“…The following 4 milk protein products were studied: WPC (lactic whey protein concentrate WPC7009; 80% protein wt/ wt), CPH (partially hydrolyzed casein MPH948; degree of hydrolysis 7.6%; 94% protein wt/wt); WPH (partially hydrolyzed whey WPH917; degree of hydrolysis 7.0%; 90% protein wt/wt); and MPH (partially hydrolyzed blend of 60:40 whey: casein MPH942; degree of hydrolysis 12-17%; 85% protein wt/wt). Note that MPH has previously been referred to as a "hydrolyzed blend" (Dalziel et al, 2017b). The protein powders were dissolved in Krebs buffer at 1 mg/mL (concentration estimated to reach the infant lower GI tract) and perfused into the tissue bath at a rate of 20 mL/min.…”
Section: Dietary Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used for measuring GI transit have been described in detail previously by Dalziel et colleagues. [22][23][24]…”
Section: Gi Transit Procedures and Measurementsmentioning
confidence: 99%
“…In dairy cows, Artegoitia et al [ 25 ] reported a better absorption of B 12 after a post-ruminal infusion of a solution of cyanocobalamin + casein hydrolysate than after infusions of cyanocobalamin + whey protein or free cyanocobalamin solutions. Proteins are known to slow gastric emptying [ 26 ] and, although both casein and whey are proteins with high B 12 -binding capacity [ 27 ], casein (hydrolyzed or not) has a gastric emptying time 33% slower than whey [ 28 ]. This may be caused by formation of curd-like structures by caseins once in the stomach whereas whey remains liquid.…”
Section: Discussionmentioning
confidence: 99%